Tindak tutur bahasa arab dalam film “The Message”: studi pragmatik - sadiyah, halimatus (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze Arabic speech acts in the film The Message through a pragmatic approach. Directed by Moustapha Akkad in 1976, the film not only portrays the early history of Islam and the life of the Prophet Muhammad (PBUH) but also serves as a medium for representing Arab cultural values and Islamic teachings to a global audience. This research employs a qualitative method with a descriptive-analytic approach. The primary data consist of Arabic dialogues from the film The Message, analyzed using John Searle’s speech act theory, which includes locutionary, illocutionary, and perlocutionary acts. The findings reveal that the speech acts in the film function not only as a means of communication but also as reflections of Arab social, religious, and moral values. Understanding the cultural context is crucial in interpreting the pragmatic meaning behind each utterance. Thus, this research contributes to cross-cultural pragmatic studies and enriches insights into religious communication through cinematic media. Penelitian ini bertujuan mengeksplorasi penggunaan tindak tutur bahasa Arab dalam film The Message melalui pendekatan pragmatik. Analisis menggunakan teori tindak tutur dari Austin dan Searle mengidentifikasi jenis tindak tutur seperti representatif, direktif, ekspresif, komisif, dan deklaratif. Penelitian ini juga mengevaluasi fungsi pragmatik dialog dalam menyampaikan nilai-nilai agama, membangun hubungan sosial, dan mencerminkan konflik historis. Hasil menunjukkan bahwa dialog dalam film ini tidak hanya alat komunikasi, tetapi juga medium penyebaran nilai budaya dan agama Islam, memperkuat solidaritas, serta menciptakan perubahan sosial di era awal Islam.